Evaluations of Internet of Things-based personal smart farming system for residential apartments - Fatin Natasya Shuhaimi; Nursuriati Jamil; Raseeda Hamzah (Institute of Advanced Engineering and Science, 2020)
Urban farming is popularly accepted by communities living in cities as they are more health-conscious and to help support the high cost of living. Unfortunately, farming takes a considerable amount of time specially to monitor the plant’s growth. Therefore, smart farming using Internet of Things (IoT) should be adopted to realize urban farming. In this study, two IoT-based smart farming system designs for personal usages in a residential apartment were proposed and evaluated. As the design was meant for beginners, two utmost parameters for maintaining plant growth was evaluated, that are humidity and temperature. The humidity and temperature readings of design A using DHT 11 sensor and design B using DHT 22 sensor were recorded for 3 days and were compared against the actual humidity and temperature of the environment. After comparing the sum of absolute difference (SAD) of both designs, the implementation costs, and the consumption power, there is an inconclusive finding in terms of accuracy and costs. However, the basic design and cost of implementing a personal IoT-based smart farming system were proposed. The factors to be considered in constructing a personal smart farming system were also described.